2003
DOI: 10.1159/000069722
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion-Induced Arrhythmias Are Suppressed by Inhibition of the Angiotensin II Type 1 Receptor

Abstract: We examined antiarrhythmic effects of drugs, including renin-angiotensin system (RAS) inhibitors, on reperfusion arrhythmias in rats in vivo. Anesthetized rats were subjected to 5 min of coronary occlusion and 30 min of reperfusion. Arrhythmia scores, calculated as the product of the type of arrhythmia (1 for ventricular tachycardia, 2 for ventricular fibrillation) and its duration (in seconds), were adopted to evaluate the severity of arrhythmias. Reperfusion arrhythmias were suppressed by Na+/H Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
(38 reference statements)
0
30
0
Order By: Relevance
“…Angiotensin II (ANG II), formed locally by mast cell-derived renin in myocardial ischemia (Mackins et al, 2006;Reid et al, 2007), is a major NHE activator via ANG II type 1 receptors (AT 1 Rs) (Reid et al, 2004) and only a minor, indirect inhibitor via AT 2 receptors (Avkiran and Haworth, 2003). ANG II elicits reperfusion arrhythmias by a direct action (Harada et al, 1998;Yahiro et al, 2003;Iravanian and Dudley, 2008), as well as by facilitating NE release (Schömig, 1990;Meredith et al, 1991;Levi and Smith, 2000); both of these actions are AT 1 Rmediated .…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II (ANG II), formed locally by mast cell-derived renin in myocardial ischemia (Mackins et al, 2006;Reid et al, 2007), is a major NHE activator via ANG II type 1 receptors (AT 1 Rs) (Reid et al, 2004) and only a minor, indirect inhibitor via AT 2 receptors (Avkiran and Haworth, 2003). ANG II elicits reperfusion arrhythmias by a direct action (Harada et al, 1998;Yahiro et al, 2003;Iravanian and Dudley, 2008), as well as by facilitating NE release (Schömig, 1990;Meredith et al, 1991;Levi and Smith, 2000); both of these actions are AT 1 Rmediated .…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with the AT 1 receptor antagonists losartan or candesartan improves recovery of function and inhibits arrhythmias in Langendorff-perfused hearts exposed to global ischemia (Lee et al, 1997;Paz et al, 1998;Wang and Sjoquist, 1999). Similar protective effects of AT 1 antagonists have been reported in in vivo models subjected to transient coronary artery ligation (Harada et al, 1998;Dorge et al, 1999;Zhu et al, 2000;Yahiro et al, 2003). Other studies, however, in intact hearts have reported that AT 1 receptor antagonists actually have deleterious effects on recovery of contractile function in reperfusion (Ford et al, 1996(Ford et al, , 1998So et al, 1998).…”
mentioning
confidence: 56%
“…The hypothesis was put forth by early experimentation, that reperfusion was a potential contributor to lethal injury of previously ischemic myocardium. 9) Protective pharmacologic agents aimed to different mechanisms administered during the reperfusion phase might be capable of limiting tissue necrosis, 10) which was demonstrated by some early experimental evidence in nonsurgical models of coronary artery occlusion-reperfusion 11,12) as well as surgical models of myocardial protection. 13) However, key aspects of inflammation and effect of antiinflammation therapy in cardiac disease are still not illustrated clearly.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] TNF-α synthesized greatly after myocardial I/R. Especially after myocardial reperfusion, the concentrations of TNF-α might have a more robust effusion, and the damage on the myocardium aggravated.…”
Section: Discussionmentioning
confidence: 99%